Pengaruh Keputusan Investasi Keputusan Pendanaan Dan Kebijakan Dividen Terhadap Nilai Perusahaan Indexs High Dividen 20 Yang Terdaftar Di BEI Pada Tahun 2017-2021 - Lara Monika; Rini Frima; Randy Heriyanto (Jurnal Akuntansi, Bisnis dan Ekonomi Indonesia (JABEI), 2023)
This study aims to examine the effect of investment decisions, funding and dividend policies on firm value. The research was conducted at High Dividend Index (IHD) companies listed on the Indonesia Stock Exchange in 2021. The research method used is descriptive verification. The data collected is secondary data, namely data regarding investment decisions, funding, dividend policies and company values ​​available from 2017 to 2021. Data obtained from the official website of the Indonesia Stock Exchange and the company's official website. The data analysis method used is panel data regression analysis. The results of the study show that investment decisions have no effect on firm value, funding decisions have an effect on firm value, dividend policy has an effect on IHD company value on the IDX in 2017-2021. Then, simultaneously, investment decision variables measured using Total Asset Growth (TAG), funding decision variables measured using the Dept to Equity Ratio (DER) and dividend policy variables measured using the Dividend Payout Ratio (DPR) have an effect on measured company value using Price Book Value (PBV).